2018
DOI: 10.1159/000488946
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Renal Function Traits: Results from the Japan Multi-Institutional Collaborative Cohort Study

Abstract: Background: Chronic kidney disease (CKD) is a rapidly growing, worldwide public health problem. Recent advances in genome-wide-association studies (GWAS) revealed several genetic loci associated with renal function traits worldwide. Methods: We investigated the association of genetic factors with the levels of serum creatinine (SCr) and the estimated glomerular filtration rate (eGFR) in Japanese population-based cohorts analyzing the GWAS imputed data with 11,221 subjects and 12,617,569 variants, and replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“… Odds ratio (95% confidence interval) indicates the risk elevation per every 10‐unit increment of the GRS. The GRS was constructed based on the count of the risk alleles of 18 eGFR‐associated SNPs on 17 and 18 that were identified in a recent GWAS in a Japanese population …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Odds ratio (95% confidence interval) indicates the risk elevation per every 10‐unit increment of the GRS. The GRS was constructed based on the count of the risk alleles of 18 eGFR‐associated SNPs on 17 and 18 that were identified in a recent GWAS in a Japanese population …”
Section: Resultsmentioning
confidence: 99%
“…After a quality check, genotype imputation was conducted based on the 1000 Genome reference panel, phase 3, using Minimac 3 software (https://genome.sph.umich.edu/wiki/Minimac3). The details of the procedure for quality control have been described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies revealed that approx. 20% of CKD cases can be linked to certain single gene variants, while others have a polygenic background with an overall heritability of 30–50% [ 194 , 195 , 196 , 197 , 198 ]. However, only 5% of these are localized in coding regions of the genes, pointing to the role of dysregulated expression.…”
Section: Mrtf In Kidney Diseasesmentioning
confidence: 99%
“…Our GWAS study provided evidence for the genetic association of SHROOM3 to the eGFR decliner. While a similar analysis has been conducted in a Japanese population of 14,539 as a discovery cohort, the role of SHROOM3 has not been confirmed 15 . This is presumably due to differences in sample size and cohort.…”
Section: Discussionmentioning
confidence: 95%